Pengaruh Perubahan Harga Emas dan Promosi terhadap Minat Nasabah Cicil Emas PT Bank Syariah Indonesia - Abizar Markin; Afrizawati Afrizawati; Agung Anggoro Seto (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
This study analyzed the influence of gold price fluctuations and promotional on customer interest in the Gold Installment product at PT Bank Syariah Indonesia Tbk, Palembang Simpang Patal Sub-Branch. A quantitative approach was employed with 100 respondents, determined using the Slovin formula and an incidental sampling technique. Data were collected through questionnaires and interviews, then processed using SPSS 26 through validity tests, reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination. The findings indicated that both partially and simultaneously, gold price fluctuations and promotions had a significant effect on customer interest, contributing 14.8 percent, while the remaining 85.2 percent was influenced by other factors outside the model. Promotion was identified as the dominant variable, implying that effective promotional strategies were key to increasing public interest in Sharia-based investments, particularly in the gold installment.